Recent advances in corporate finance - Altman, Edward I., 1941-; Subrahmanyam, Marti G., 1946- (Homewood, Ill. : R.D. Irwin, 1985)
The text attempts to improve the interface between the worlds of academia and practice and also to highlight some of the more significant trends and seminal works in the field of corporate finance.
Includes bibliographica references and indexes.
oif 15/10/14
Loan
Keywords: Corporations -- Finance